Sin Returns To Sociology - MacIntyre, Alasdair (The Hastings Center report, 1979)
Book reviewed in this article: The Seven Deadly Sins: Society and Evil. By Stanford M. Lyman. The Seven Deadly Sins Today. By Henry Fairlie.